2022
DOI: 10.3390/cancers14174338
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Thyroid Surgery in a University Hospital in South Korea

Abstract: The COVID-19 pandemic has changed healthcare systems around the world. Medical personnel concentrated on infectious disease management and treatments for non-emergency diseases and scheduled surgeries were delayed. We aimed to investigate the change in the severity of thyroid cancer before and after the outbreak of COVID-19 in Korea. We collected three years of data (2019, 2020, and 2021) on patients who received thyroid surgery in a university hospital in South Korea and grouped them as “Before COVID-19”, “Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…When the post-pandemic group was compared to the pre-pandemic group, the current study found that the number of thyroid surgeries had increased and that the cancer rate in the final histopathology was not only higher, but also more invasive and had more aggressive pathological findings. This finding partially aligned with findings from Asia and Romania, which described a reduction in total thyroidectomy numbers but an increase in aggressive thyroid variants [ 8 , 23 , 26 ]. However, the rise in cancers with more aggressive behavior cannot be explained by delayed diagnosis and treatments for two reasons: firstly, the circumstances of COVID-19 management in Abu Dhabi, where there was no restriction for citizens to access healthcare facilities; secondly, the fact that PTC is relatively slow-growing and may be survived without immediate treatment, as reported by Ito et al in the biggest prospective series of active surveillance patients at Kuma Hospital over 22 years.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When the post-pandemic group was compared to the pre-pandemic group, the current study found that the number of thyroid surgeries had increased and that the cancer rate in the final histopathology was not only higher, but also more invasive and had more aggressive pathological findings. This finding partially aligned with findings from Asia and Romania, which described a reduction in total thyroidectomy numbers but an increase in aggressive thyroid variants [ 8 , 23 , 26 ]. However, the rise in cancers with more aggressive behavior cannot be explained by delayed diagnosis and treatments for two reasons: firstly, the circumstances of COVID-19 management in Abu Dhabi, where there was no restriction for citizens to access healthcare facilities; secondly, the fact that PTC is relatively slow-growing and may be survived without immediate treatment, as reported by Ito et al in the biggest prospective series of active surveillance patients at Kuma Hospital over 22 years.…”
Section: Discussionsupporting
confidence: 86%
“…Tissue-specific malignancies require individualized treatment plans due to their varying malignancy and aggressiveness. If treatment for diseases such as melanoma, non-small-cell lung cancer, or acute myeloid leukemia is delayed, the patient’s prognosis worsens significantly [ 10 , 23 ]. In contrast, patients with indolent tumors, such as most prostate cancers or differentiated thyroid carcinomas, may be able to wait for a while before experiencing any signs of malignancy [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social distancing measures and the state of lockdown have profoundly affected the healthcare system in almost all parts of the world ( 17 ). As the medical team focused primarily on COVID-positive patients, newly implemented oncology guidelines recommended short-term deferral of certain procedures and surgeries, including cases of aggressive cancers such as gastric, pancreatic, genitourinary, or melanoma ( 14 , 18 ). Some studies have shown that 38.7% to 59% of cancer patients were advised to delay treatment ( 12 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent World Health Organization (WHO) report estimates that in 2020, 449,000 new cases were diagnosed in female and 137,000 in male patients ( 13 ). Taking into consideration that thyroid cancer has a much more favorable outcome compared to other types of malignant tumors, recent guidelines mention that the diagnosis and surgical intervention could be postponed during the COVID-19 pandemic without detrimental effects on the patient’s survival and prognosis ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, an adverse development of cardiac emergency care has been reported with inexplicable low numbers, i.e., of myocardial infarction, during phases of high COVID-19 incidence [ 25 ]. Further articles show that this development does not only apply to medicine but also to emergency and elective surgery of all kinds [ 4 , 5 , 26 , 27 ]. Di Martino et al provide an interesting study that connects the fields of oncology with surgery by assessing the variations in elective oncological surgery on colorectal and breast cancer during the first pandemic year of 2020 in comparison to the previous years of 2018 and 2019.…”
Section: Discussionmentioning
confidence: 99%